Analysis of the anatomic relationship of the infraorbital canal with the roots of the maxillary fourth premolar tooth in the three different skull types: Mesocephalic, brachycephalic, and dolichocephalic, using cone beam computed tomography - Littles, Maria E.; Rao, Sangeeta; Bannon, Kristin M. (Frontiers in Veterinary Science, 2022)
The objective of this retrospective descriptive study was to describe variations in the anatomic position of the infraorbital canal relative to the mesial and distal roots of the maxillary fourth premolar tooth for the three canine skull types (mesocephalic, brachycephalic, and dolichocephalic) using cone beam computed tomography. The study evaluated the position of the infraorbital canal in 120 canine patients (240 teeth) that presented to a private dentistry referral practice for reasons unrelated to the study. There were 40 patients for each skull type, determined by breed and facial index calculation. A grid system was used to determine the anatomic positions of the infraorbital canal relative to the roots of the maxillary fourth premolar tooth. The infraorbital canal's most frequent position at the mesial roots level for the total population (38.8%) and the mesocephalic skull type (53.8%) was apical to the furcation. For the brachycephalic (40.0%) and the dolichocephalic skull types (40.0%), the most frequent position was partially in the furcation and partially apical to the furcation. The most frequent position of the infraorbital canal at the level of the distal root was apical and palatal to the distal root for the total population (36.7% ), the mesocephalic skull type (42.5%), and the brachycephalic skull type (35.0%). For the dolichocephalic skull type, the most frequent location of the infraorbital canal was both directly palatal and partially apical and palatal to the distal root (42.5%). For the brachycephalic skull type, the distal root was most frequently positioned caudal to the maxillary foramen/floor of the orbit (62.5%). Based on these findings, extra care must be taken with the dolichocephalic and the brachycephalic skull types to avoid iatrogenic trauma to the infraorbital canal and the orbit during surgical procedures on the maxillary fourth premolar tooth.